2018
DOI: 10.1111/pce.13391
|View full text |Cite
|
Sign up to set email alerts
|

Revealing mechanisms of salinity tissue tolerance in succulent halophytes: A case study for Carpobrotus rossi

Abstract: Efforts to breed salt tolerant crops could benefit from investigating previously unexplored traits. One of them is a tissue succulency. In this work, we have undertaken an electrophysiological and biochemical comparison of properties of mesophyll and storage parenchyma leaf tissues of a succulent halophyte species Carpobrotus rosii ("pigface"). We show that storage parenchyma cells of C. rossii act as Na sink and possessed both higher Na sequestration (298 vs. 215 mM NaCl in mesophyll) and better K retention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…The maintenance of high cytosolic K + levels under saline conditions is essential for enzymatic activities, appropriate metabolic processes, ionic homeostasis, charge balance, and the prevention of cell death induced by high salinity (Shabala and Cuin, 2008; Shabala, 2009; Demidchik et al , 2010). A causality between the superior ability for K + retention (especially in roots) and plant salt tolerance has been established in various species (Chen et al , 2005; Cuin et al , 2008; Sun et al , 2009 a ; Bose et al , 2015; Chakraborty et al , 2016; Yu et al , 2016; Zeng et al , 2018). Here, we showed that under saline conditions, 6 x I. trifida possessed better capacity for the maintenance of K + levels and restriction of Na + accumulation in root and leaf tissues than 2 x I. trifida (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of high cytosolic K + levels under saline conditions is essential for enzymatic activities, appropriate metabolic processes, ionic homeostasis, charge balance, and the prevention of cell death induced by high salinity (Shabala and Cuin, 2008; Shabala, 2009; Demidchik et al , 2010). A causality between the superior ability for K + retention (especially in roots) and plant salt tolerance has been established in various species (Chen et al , 2005; Cuin et al , 2008; Sun et al , 2009 a ; Bose et al , 2015; Chakraborty et al , 2016; Yu et al , 2016; Zeng et al , 2018). Here, we showed that under saline conditions, 6 x I. trifida possessed better capacity for the maintenance of K + levels and restriction of Na + accumulation in root and leaf tissues than 2 x I. trifida (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in NaCl-induced K + efflux from root tissues may help plants to achieve K + homeostasis at the whole-plant level under saline conditions (Shabala and Pottosin, 2014). The magnitude of NaCl-induced K + efflux is strongly correlated with cellular K + retention and salt tolerance in a broad range of species, including barley (Chen et al , 2005), wheat (Cuin et al , 2008), poplar (Sun et al , 2009 a ), sweet potato (Yu et al , 2016), Brassica species (Chakraborty et al , 2016), and halophytes (Bose et al , 2015; Zeng et al , 2018). The following mechanisms mediate K + efflux from root tissues in salinized plants: (i) depolarization-activated outward-rectifying K + -permeable channels (DA-KORCs); (ii) weakly voltage-dependent non-selective cation channels (NSCCs); and (iii) reactive oxygen species (ROS)-activated K + -permeable channels (including KORCs and NSCCs) (Shabala et al , 2016 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, GR protein content enhanced in all salt treatments except 600 mM NaCl treatment. Previous studies have reported that GR has a protective role against salinity-induced oxidative damage in different plant species (Zeng et al 2018;Parida and Jha 2010). High antioxidant enzyme activities and the protein contents in S. hieraciifolia exposed to excess salinity showed that the plant can effectively induce the antioxidant system to survive excess salt.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, Shabala and Mackay (2011) recorded that succulent structures were associated with an increase in mesophyll cell size and the relative size of their vacuoles, a decrease in surface area per tissue volume, and high water content per unit surface area. Zeng et al (2018) investigated some antioxidant enzyme activities in succulent halophyte Carpobrotus rosii suggested that salt stress resulted in significant increases in activities of major antioxidant enzymes, such as APX, CAT and GR and decrease in SOD activity in the mesophyll tissue. Likewise, non-succulent extreme-halophyte Thellungiella parvula, a halophytic relative of Arabidopsis (Arabidopsis thaliana), could regulate ion hemostasis by providing osmotic adjustment and alleviate hazardous effects of excess salinity by inducing antioxidant system (Uzilday et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have conducted on the salinity tolerance mechanism of succulent halophytes or extreme halophytes. For instance, Zeng et al (2018) investigated some antioxidant enzyme activities in succulent halophyte Carpobrotus rosii suggested that salt stress resulted in significant increases in activities of major antioxidant enzymes, such as ascorbate peroxidase (APX), catalase (CAT) and glutathione reductase (GR) and decrease in superoxide dismutase (SOD) activity in the mesophyll tissue. Likewise, extreme-halophyte Thellungiella parvula, a halophytic relative of Arabidopsis (Arabidopsis thaliana), could regulate ion hemostasis by providing osmotic adjustment and alleviate hazardous effects of excess salinity by inducing antioxidant system (Uzilday et al, 2015).…”
Section: Introductionmentioning
confidence: 99%